Innovative Approaches To Public Employment Governance In Context of The Labor Market Transformation - Radmyla VOITOVYCH; Galyna KRAPIVINA; Iryna SURINA; Mieczysław DUDEK; Hennadii DMYTRENKO (Communications of International Proceedings, 2021)
The article summarizes the arguments and counterarguments in the framework of a scientific discussion about innovative approaches to employment and non-standard forms of volunteering, voluntourism, virtual employment and agency labor. The article presents the results of empirical analysis, which showed that the system-ontological approach can be recommended as innovative for meaningful analysis and functional modeling of the subject area of employment; the onto-gnoseological model of employment provides a holistic view of the subject area of public administration, which ensures a systematic nature of its study. System-ontological analysis allows to reconstruct on a scientific basis the missing logical connections of the subject area in their entirety. The study empirically confirms and theoretically proves that the innovative adjustment of employment can be based on the classification series of the subject area mechanisms of public employment management. The research results can be useful for determining the explicit and deep ontological meaning, general evolution and trends in the mechanisms of public administration in employment management.
Keywords: Public Administration; Employment; Onto-Epistemological Model; Logical-Semantic Model